Investment cooperation between Spain and China - A. Aviliova (Ибероамериканские тетради)
In 2018, Spain and China signed a package of investment agreements opening a new stage in their economic cooperation. Both parties expect to develop production cooperation, including in technologically advanced industries. China is rapidly expanding its investment presence abroad. However, the offensive nature of its investment policy creates certain obstacles and risks for the EU countries, which Spain has to reckon with.